Thrombocytopenia in the Setting of Hemodialysis Using Biocompatible Membranes - Kathryn B. Muir; Clifford D. Packer (Case Reports in Medicine)
Thrombocytopenia is a known potential side effect of hemodialysis, however, it is rarely seen in patients who undergo hemodialysis using biocompatible membranes. This case demonstrates hemodialysis-associated thrombocytopenia with use of biocompatible dialysis membranes that expose blood directly to polysulfone. The thrombocytopenia resolved in this patient when the dialysis membrane was changed to a biocompatible model with a polyethylene glycol barrier layer preventing direct interaction between patient blood and polysulfone. The calculated Naranjo ADR score of 9 indicates a highly probable adverse reaction.